Pengaruh Substitusi Pati Ganyong (Canna edulis ker) terhadap Tekstur, Komposisi Proksimat dan Daya Terima pada Pembuatan Dodol - Nadia, Izzatun, Dwi Sarbini, S.ST., M.Kes, Rusdin Rauf, S.TP., MP (2016)
Dodol is one of Indonesian food made from glutinous rice flour, coconut milk and sugar. Canna strach can be used as a substitute material of glutinous rice flour in making dodol. The substitution of canna strach affect in the texture of dodol, so it's necessary to test the texture. The quality of food is also determined by the nutritional content, the proximate compotition testing of dodol canna is also required. The aim of the study was to know the effect of canna starch as a substitute of glutinous rice flour in making dodol. Completely randomized design was used, with four levels of canna starch substitution, were 0%, 25%, 50%,and 75% with three replications. Texture was measured with tensile strength test. Proximate composition including moisture, ash, protein, fat and carbohydrates were tested using by different method. The acceptance of the product was tested by untrained panelists. The results indicated that there was a significant effect of canna starch substitution on dodol texture.the higher the substitution of canna starch, the lower the texture of dodol. The highest of the texture of dodol was gave by 0% substitution, followed by 25%. Proximate compotition of dodol showed that there was an effect of canna starch substitution on protein on dodol. However, there was no effect on moisture, ash and fat contens. The highest acceptance of dodol gave by 0% substitution, followed by 25% substitution. There is an effect of canna starch substitution on texture, proximate compotition and acceptance level of dodol.